Pengembangan E-Modul Fisika Dasar untuk Mahasiswa Calon Guru SMK Teknik Konstruksi dan Properti - M. Agphin Ramadhan; Santoso Sri Handoyo; M. Mahameru Alfarisi (Department of Physics Education, Universitas Mataram, 2020)
Students of the Building Engineering Education (PTB) study program, as prospective teachers of the Construction and Property Engineering Vocational School (TKP), need to master physics subject matter extensively and deeply. Hopefully, when they become teachers, vocational students can be interested in physics subjects. This study aims to produce an e-module for introductory physics courses for prospective TKP SMK teachers. This study uses the Research and Development (R&D) method and uses the 4D development model, which consists of four main stages: Define, Design, Development, and Disseminate. Feasibility assessment by media experts obtained a percentage of the validity of the e-module by 90% and included in the very feasible category in terms of media. The feasibility assessment by material experts obtained an average percentage of e-module validity data that is 82%, and it falls into the very feasible category in terms of material. The limited trial results showed that the mean score of participants during the pre-test was 64, and there was an increase to 89 after following the post-test. The results of the product user assessment obtained a value of 84.8 in the very feasible category. The results of validation tests and user responses concluded that the e-module for introductory physics courses is very suitable for teaching material for PTB students, prospective TKP vocational teachers.